Minutes of the 1st Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 1st Meeting of the Academic Council of BRAC University held on Monday, 24th September, 2001